2023
DOI: 10.1371/journal.pone.0284646
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with Hepatitis B virus infection among pregnant women attending public hospitals in Addis Ababa, Ethiopia

Abstract: Background Hepatitis B Virus (HBV) infection is one of the serious public health problems worldwide and is a major cause of morbidity and mortality. Viral hepatitis during pregnancy poses problems like a high risk of maternal complications, mother-to-child transmission (MTCT), and challenges in the management of drugs. This study aimed to determine the magnitude of HBV infection and associated risk factors among pregnant women who attended public hospitals in Addis Ababa, Ethiopia. Method A multicenter prosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
(82 reference statements)
1
4
0
Order By: Relevance
“…The risk factor that associated with the hepatitis b among pregnant women in kupang city was having >1 sexual partners, this finding is in agreement with study conducted among pregnant women in DKI Jakarta that found that having >1 sexual partner is the risk factor of hepatitis B and pregnant women who have >1 sexual partner (Eba et al, 2021;Umare et al, 2016). As one of sexual transmitted disease during sexual contact Hepatitis B Virus will migrate which increases with the duration of sexual activity and the number of sexual partners (Tesfu et al, 2023), moreover when it is unprotected and is done with multiple partners, the transmission rate will be increased (Alemu et al, 2020). The transmission of hepatitis B among pregnant women could be found from the sexual partners that might having connection to free sex, contact with body fluids such as blood, semen and vaginal mucus (Kenea & Lemessa, 2020).…”
Section: Discussionsupporting
confidence: 88%
“…The risk factor that associated with the hepatitis b among pregnant women in kupang city was having >1 sexual partners, this finding is in agreement with study conducted among pregnant women in DKI Jakarta that found that having >1 sexual partner is the risk factor of hepatitis B and pregnant women who have >1 sexual partner (Eba et al, 2021;Umare et al, 2016). As one of sexual transmitted disease during sexual contact Hepatitis B Virus will migrate which increases with the duration of sexual activity and the number of sexual partners (Tesfu et al, 2023), moreover when it is unprotected and is done with multiple partners, the transmission rate will be increased (Alemu et al, 2020). The transmission of hepatitis B among pregnant women could be found from the sexual partners that might having connection to free sex, contact with body fluids such as blood, semen and vaginal mucus (Kenea & Lemessa, 2020).…”
Section: Discussionsupporting
confidence: 88%
“…The current study showed no association between HBV and age of participants (p value 0.512), which is consistent with a study's findings conducted in Yemen 21 , Jordan 28 , Uganda 29 , and in Nigeria 31 . However, it differs from studies carried out in Yemen30 , Saudi Arabia 27 , China 10 , Ethiopia16 , USA32 and in Greece13 . This study reported that there was strong association between HBV infection and educational level of pregnant women (p value 0.000).…”
mentioning
confidence: 61%
“…However, routine screening of pregnant women for HBsAg is yet to be implemented in some other countries' prenatal care programmes, and even in Western countries, some pregnant women have never been tested for HbsAg 13 . HBV infection prevalence rate of 0.1% in the Northwest to 1-4% in the South of Europe, 0.5% in Russia 14 , 5.2% in Pakistan 15 , 11.7% in China 10 , 3.04% in Ethiopia 16 , 2.2% in Egypt 17 and 1.5% in Oman 18 were reported in pregnant women. In spite of the current availability of an HBV vaccine.…”
Section: Introductionmentioning
confidence: 96%
“…Hepatitis B virus (HBV) is a substantial global public health issue [ 7 – 9 ] and belongs to the hepadnavirus family, a group of deoxyribonucleic acid (DNA) viruses [ 2 ]. It primarily affects the liver and can lead to both short-term and long-term health problems [ 8 , 9 ], resulting in significant levels of illness and death [ 7 , 10 14 ]. World Health Organization (WHO) estimates that 254 million people will be living with chronic hepatitis B infection in 2022 [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The majority of pregnant women, however, do not receive routine screening during antenatal care (ANC) [ 27 ]. For both the mother and the new-born, an HBV-complicated pregnancy causes challenges in the management of drugs or medication administration [ 14 ]. Despite a potent vaccination, HBV infection remains one of the significant public health issues, primarily in developing nations [ 28 ].…”
Section: Introductionmentioning
confidence: 99%